Makna Simbolik Perjalanan Apostolik Paus Fransiskus di Indonesia dan Penerimaannya oleh Publik: Memperkuat Persaudaraan Antaragama - Setiawan, Dede; Kamilia, Adila (Integritas Terbuka: Peace and Interfaith Studies, 2025)
This study analyzes the symbolic meaning of Pope Francis' apostolic journey to Indonesia in September 2024, using George Herbert Mead's Symbolic Interaction Theory. The research focuses on how the symbolic actions, words, and objects during the visit were interpreted by Indonesian society, particularly in the context of interfaith relations. The study employs a qualitative approach, utilizing literature study techniques to analyze primary sources such as official documents, speeches, and media reports, as well as secondary sources like academic journals and books. The findings reveal that Pope Francis' visit carried profound symbolic meanings, particularly through his gestures (e.g., kissing the hand of the Grand Imam of Istiqlal Mosque), speeches, and the signing of the Istiqlal Declaration on Religious Harmony. These actions were widely perceived as promoting interfaith dialogue and solidarity, although some skepticism existed among certain groups. This research contributes to the understanding of how symbolic interactions can foster interfaith harmony in a multicultural society like Indonesia, offering insights for future studies on religious diplomacy and public reception of symbolic actions.